IMPLEMENTATION OF JSON WEB TOKEN IN THE DEVELOPMENT OF VILLAGE MONOGRAPH DATABASE BASED ON RESTAPI - Ramadhan, Akhmad; Mulyati, Sri (Informatika, Universitas Jenderal Soedirman, 2024)
Currently, both central and local government institutions have been utilizing technological advancements to optimize services, strengthen partnerships, and maximize management efficiency. However, this has led to discrepancies in data across various government platforms due to the absence of an integrated database that can be linked with multiple institutional platforms. The development of an integrated database has become crucial to ensure data consistency and prevent discrepancies across different platforms. This study aims to develop an integrated database for village monographs by leveraging data transfer technology based on REST API and implementing security using JSON Web Token (JWT). The database development was carried out using the prototype development method, and testing was conducted using the black-box testing method. The results show that this research successfully developed a database capable of operating effectively on two different platforms, and the system developed adheres to the security standard of JSON Web Token. Therefore, this study can improve the efficiency of managing village monograph data while ensuring data protection during the transfer process between platforms.